Rapid and high-throughput analysis of 5-hydroxymethylfurfural in honey by MALDI-MS with in-situ tetra (4-aminophenyl)-porphyrin derivatization - Zhi Sun; Fangfang Wang; Peipei Zhou; Di Chen; Lihua Zuo (npj Science of Food)
Abstract 5-Hydroxymethylfurfural (HMF), a product of the Maillard reaction and caramelization in honey, serves as a crucial marker of food quality and thermal processing, underscoring the importance of regulatory surveillance for consumer safety. This study introduces a method for rapid, high throughput and eco-friendly detection of HMF, using derivatization in matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS). 5,10,15,20-Tetrakis-(4-aminophenyl)-porphyrin was employed for in-situ derivatization of aldehydes after extraction by ethyl acetate, enhancing detection sensitivity by shifting low-molecular-weight aldehydes to higher regions. The calibration curves for HMF determination exhibited outstanding linearity. The detection limit reached 0.347 mg/kg with good accuracy and precision. Variations in the content of HMF in honey during heating were also assessed, revealing the increased formation of HMF under high temperature and prolonged heating. The method’s proficiency was evidenced through the detection of various aldehydes. This method represents an advance in rapid analysis for food safety, aligning with green chemistry principles.